A Comparative Study of HPV Vaccine Acceptability Across Global North and South Countries: USA and Kenya - Robert Nyaga; Adu Gyamfi Prince (Communicare)
This study examined the HPV vaccine landscape in Kenya and the USA with a focus on if differences exist in the perceptions of HPV knowledge, vaccine attitudes, subjective norms, perceived behavioural control, and vaccine intention among students across country and gender. It also provides useful findings that can inform the design of persuasive health messages to promote the uptake of HPV vaccines among college students in Kenya and the USA. The study used surveys to recruit 1,033 participants (511 Kenyan and 522 USA students). The two-way MANOVA analysis revealed that the multivariate main effects showed no significant differences for gender, but the results revealed a significant main effect for the country. However, the interaction between gender and country of the participants was not significant. The univariate analysis revealed that the participants of the two countries had small significant differences in their subjective norms about HPV vaccination, and perceived behavioural control. The correlation analysis showed that HPV knowledge correlates with knowledge about the HPV vaccine and country, but not with gender. The results also revealed that knowledge about the HPV vaccine correlates with both gender and country. These results highlight the most salient predictors of vaccination intentions among college students that health communicators can focus on when designing and implementing HPV vaccination campaigns targeting students in Kenya and the USA.